A system for the measurement of impact force in footwear - Bauer, D.; Zerpa, C.; Valjakka, K.
The purpose of the research was to develop a mechanical device to measure the effectiveness of the Energy (J) absorption in materials used for the construction of the soles of athletic footwear. Mean Ground Reaction Force curves were used to calculate energy during impact loading in the materials used for the soles of six different brand-name running shoes. Results indicated a range of variability in energy absorption in the soles of the shoes and the relationship to shoe quality assessed on retail cost. The measurement system provided a reliable and alternate measure of performance in shoe materials and demonstrates a need for the provision of more accurate and alternative test measures for the consumer.